(untitled) (Research, Society and Development, 2022)
Wastewater treatment has taken on an important role in public health aspects since most of the diseases that plague developing countries comes from poor quality water. Thus, the present work aims to analyze the level of organic matter and bacteria Escherichia coli of a effluent treated by a biodigestor fossa system installed on the Bravo site belonging to the municipality of Boa Vista-PB. The study was conducted from August 2021 to October 2022. During this period visits were reailed to characterize the area, as well as a biodigesto fossa system to treat the sewage processed by the sanitary vessel of an eight people residence. Given the fermentation process the effluent was treated and collected at the exit of the fourth water tank for pH analysis, Biochemical Demand for Oxygen (BDO) and Escherichia coli. Thus, after the five months of operation of the system the final effluent presented pH and Escherichia coli within the recommended by CONAMA Resolution 357/2005. The BDO results were above the recommended, but it does not become a limiting factor to its agricultural use as it is not used irrigation system that can be prejudicked with possible clogging. Thus, the system presents effluent conducive to irrigation of forage palm (Opuntia ficus-indica (L.) Mill.), contributing to the community’s quality of life and reducing environmental, social impacts and strengthening the local economy.